Intelligence, Non-Intelligence … Let's Call the Whole Thing Off. Issue 4 (2nd October 2018) - Pryor, Adam
ABSTRACT: Astrotheology, not simply a theology of space sciences, is necessary because astrobiology effects a conceptual shift in how we ask the question "Why do we exist?" Here I suggest characterizing that shift in terms of the intra-action of living systems and habitable environments, which has serious implications for approaches to doctrinal theology. I consider this in terms of the imago Dei and what implications a transdisciplinary approach to astrotheology might in turn have for reframing SETI and METI endeavors as a quest for an Extraterrestrial imago Dei (SETiD or METiD).